HUBUNGAN PENGAWASAN OLEH MANAJER DENGAN EFEKTIVITAS KERJA PEGAWAI PADA PT. PLN (PERSERO) RAYON JATIBARANG - Yudi Riyanto; Achdi Halim; Nurudin Siraj (Jurnal Ilmiah Publika, 2013)
This thesis entitled " Relationship With Manager Control By Employees At Work Effectiveness PT PLN ( Persero ) Rayon Jatibarang " . The problem in this study is the lack of achievement of employee effectiveness caused by less than optimal supervision by managers PT.PLN ( Persero ) Jatibarang Rayon . The purpose of this study was to determine how the relationship Oversight By Manager Effectiveness Working With Employees In PT PLN ( Persero ) Jatibarang Rayon . The research hypothesis is that the authors propose " There is a positive and significant relationship between the Supervisory Relationship Manager By Employees At Work With The effectiveness of PT PLN ( Persero ) Rayon Jatibarang " . Statistical hypothesis , namely , Ho ( null hypothesis ) count = rs < rs table (no significant positive relationship between Oversight By Manager Work With Employee Effectiveness ) and Ha ( Alternative Hypothesis ) count = rs > rs table ( there is a positive relationship and By significantly between Control Manager Effectiveness Working With Employees ) . The method I use in this thesis is a survey method . Methods of survey research that is done on large populations and small population , but the data is the data of the studied samples diamil of the population , while according to the level eksplanasinya the writer in the research study is associative ( relationship ) , correlation method were looking for how much the relationship among the variables x ( supervision ) with variable y ( effectiveness ) . Data analysis technique used is quantitative analysis ( data in the form of numbers or statistical formula as data processing ) . And hypothesis testing using the Spearman rank correlation coefficient formula . The population in this study amounted to 20 respondents . Sampling technique using sampling techniques Saturated ( Engineering Census ) . Based on the results obtained that the variable Oversight By PT.PLN Manager ( Persero ) Jatibarang Rayon is good enough , yet less than optimal . As can be seen from the success of its implementation which reached 58.53 % with a total score of 878 . Variable Effectiveness At Work Employee PT PLN ( Persero ) Rayon Jatibarang are pretty good at the interval level . This is evident from the total score of 491 or 61.37 % . Relationship Between Supervision By Manager With Employees At Work Effectiveness PT PLN ( Persero ) Jatibarang Rayon is at the level of correlation is quite good , where the calculated value of 0.647 rs , rs As compared with a table for 20 people for a number of respondents 0.377 , then2the value is significant . With the hypothesis that the authors proposed and tested acceptable